UJI EFEKTIVITAS BEBERAPA JENIS PERANGKAP TERHADAP KUMBANG TANDUK (Oryctes rhinoceros L.) (COLEOPTERA; SCARABAEIDAE) - Rieske Luhukay; Betty Sahetapy; Aminudin Umasangadji (Universitas Pattimura, 2017)
The objective of this study was to determine the types of traps that were effective in trapping horn beetles (O. rhinoceros L.). The research was conducted in Latuhalat Village, Nusaniwe District, Ambon Municipality, from September till November 2016. The treatment consisted of light trap, pheromone trap and pheromone and light trap. Observations were done on the number of imago of O. rhinoceros L. trapped and its sex ratio on each treatment. The results showed that pheromone trap was the most effective trap on O. rhinoceros L.